Revitalising critical components of urban decay features - A. Alias,; Z. Zyed,; Chai, W.W. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Conservation and sustainability of historic cities in Malaysia have been drawing a lot attention from different stakeholders as many researches were undertaken relating heritage conservation and heritage tourism. The declaration of historic cities in Penang and Malacca as World Heritage Cities by UNESCO had proven that the conservation and preservation of tangible heritage assets not only essential to sustain the continuity of local cultural identity but also contribute to the economic regeneration and domestic heritage tourism. However, there have been only a small number of studies done on the urban decay features experienced by old towns in Malaysia and the corresponding revitalisation tools which suit the local culture context. Based upon the conflicts between urban decay issues arise within Ipoh Old Town and the lack of effective revitalisation efforts, the objectives are to identify the urban decay features currently experienced by Ipoh Old Town and to recommend the critical components to be revitalised in Ipoh Old Town. The mixed methods research which incorporated both quantitative and qualitative research approaches is adopted as the methodology for this study. The quantitative data is obtained through questionnaire surveys whereas the qualitative research methods involved the gathering of information through interviews and case study analysis. These suggestions are categories into three major themes which are revitalisation, stricter enforcement and financial funding.